Clinical application of confocal laser endomicroscopy in neurosurgery: a scoping review - Xu, Yuan; Calderon-Valero, Carlos E.; On, Thomas J.; Restelli, Francesco; Acerbi, Francesco; Schlegel, Jürgen; Belykh, Evgenii; Preul, Mark C. (Frontiers in Surgery, 2026)
BackgroundConfocal laser endomicroscopy (CLE) is an emerging intraoperative “optical biopsy” tool that enables real-time, in vivo, cellular-resolution visualization of brain tumor histoarchitecture. It offers the potential to complement frozen section pathology by providing rapid intraoperative feedback. We conducted a scoping review of prospective clinical studies to characterize CLE platforms, fluorophores, operative applications, and diagnostic performance in neurosurgical patients.MethodsThis review followed PRISMA-ScR guidelines. A systematic search of PubMed, Scopus, and Embase was performed. Eligible studies were prospective clinical studies of intraoperative CLE imaging in neurosurgical patients. Two independent reviewers screened and extracted data on study design, CLE system, fluorophore use, pathology types, diagnostic performance, and workflow characteristics.ResultsFrom 379 initial records, 19 studies met final inclusion criteria, with most (63%) in the past five years. Five CLE platforms were studied: CONVIVO (47%), FIVE1 (16%), Cellvizio (16%), EndoMAG 1 (11%), and cCeLL (11%). These CLE systems use different fluorophores that lead to distinct image characteristics. Across tumor types, CLE demonstrated diagnostic accuracy comparable with frozen section, with reported sensitivity up to 93% and specificity up to 94% in certain scenarios. CLE interpretation was feasible within minutes, faster than frozen section, and several studies reported successful integration with fluorescence-guided surgery and telepathology platforms.ConclusionsClinical evidence supports the feasibility, safety, and efficiency of CLE in neurosurgery, offering rapid intraoperative histology without tissue removal. Current studies remain observational with varying study design and outcome definition, limiting assessment of the effectiveness and impact. Well-designed interventional trials are needed to determine CLE's definitive role as an intraoperative optical biopsy tool guiding tumor resection and patient outcomes.